Management of maxillofacial trauma in the elderly: A European multicenter study. Issue 3 (9th January 2020) - Brucoli, Matteo; Boffano, Paolo; Romeo, Irene; Corio, Chiara; Benech, Arnaldo; Ruslin, Muhammad; Forouzanfar, Tymour; Starch‐Jensen, Thomas; Rodríguez‐Santamarta, Tanía; de Vicente, Juan Carlos; Snäll, Johanna; Thorén, Hanna; et al.
Abstract: Background/Aims: Management of maxillofacial trauma in the geriatric population poses a great challenge due to anatomical variations and medical comorbidities. The aim of this study was to analyze the management variables, timing, and outcomes of facial fractures in elderly patients (aged 70 years or more) at several European departments of oral and maxillofacial surgery. Materials and Methods: This study was based on a systematic computer‐assisted database that allowed the recording of data from all geriatric patients with facial fractures from the involved maxillofacial surgical units across Europe between 2013 and 2017. Results: A total of 1334 patients were included in the study: 665 patients underwent closed or open surgical treatment. A significant association ( P < .005) was found between the presence of concomitant injuries and a prolonged time between hospital admission and treatment. The absence of indications to treatment was associated with comorbidities and an older age ( P < .000005). Conclusions: Elderly patients require specific attention and multidisciplinary collaboration in the diagnosis and sequencing of trauma treatment. A prudent attitude may be kept in selected cases, especially when severe comorbidities are associated and function is not impaired.